2013
DOI: 10.1063/1.4824891
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of superconductivity in Nb by IrMn in IrMn/Nb bilayers

Abstract: Effect of antiferromagnet on superconductivity has been investigated in IrMn/Nb bilayers. Significant suppression of both transition temperature (Tc) and lower critical field (Hc1) of Nb is found in IrMn/Nb bilayers as compared to a single layer Nb of same thickness; the suppression effect is even stronger than that of a ferromagnet in NiFe/Nb bilayers. The addition of an insulating MgO layer at the IrMn-Nb interface nearly restores Tc to that of the single layer Nb, but Hc1 still remains suppressed. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The curve of S Ta is typical for these systems with Nb thickness around 500 Å [7], presenting a T C of 5.9 K. For S Nb , T C was reduced to 5.3 K and, unexpectedly, the transition is formed by two well-defined regions (two steps) with different features and slopes. Here it is important to point out that the transitions in these curves are related only to the Nb spacer layer, because the T C of the thinner Nb buffer layer (150 Å) is about 2.23 K [14] and may be suppressed or reduced by the IrMn layer, as was observed in IrMn/Nb bilayers by Wu et al [15].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The curve of S Ta is typical for these systems with Nb thickness around 500 Å [7], presenting a T C of 5.9 K. For S Nb , T C was reduced to 5.3 K and, unexpectedly, the transition is formed by two well-defined regions (two steps) with different features and slopes. Here it is important to point out that the transitions in these curves are related only to the Nb spacer layer, because the T C of the thinner Nb buffer layer (150 Å) is about 2.23 K [14] and may be suppressed or reduced by the IrMn layer, as was observed in IrMn/Nb bilayers by Wu et al [15].…”
Section: Introductionmentioning
confidence: 91%
“…Peña et al have synthesized structures containing FM/ SC interfaces composed of La 0.7 Ca 0.3 MnO 3 (FM) and YBa 2 Cu 3 O 7 (SC) and found a magnetoresistance in excess of 1000%, which is directly associated with the superconductivity of the YBa 2 Cu 3 O 7 layer [3]. Stamopoulos 15 / Nb multilayers have found that without an applied magnetic field the multidomain configuration of the FM layer supports the nucleation of superconductivity [4]. In contrast the superconductivity is suppressed, if the FM layer is saturated in monodomain state.…”
Section: Introductionmentioning
confidence: 98%
“…In antiferromagnet/superconductor heterostructures, suppression of T C [15][16][17][18] was reported with Cr and IrMn antiferromagnets, whereas Josephson current in superconductor/antiferromagnet/superconductor trilayers [16,[19][20][21][22] was observed with Ca 1−x Sr x CuO 2 , Cr, and FeMn antiferromagnets. More recently, electrical and thermal phenomena specific to antiferromagnet/superconductor junctions were theoretically predicted, as the result of combined specular reflection of holes and retroreflection of electrons [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potential of using antiferromagnets in superconducting spintronics has been recognized. For instance, at the interface between an antiferromagnet and a superconductor, normal reflection and AR have been demonstrated to be both specular and retroreflective [49][50][51][52][53][54][55][56][57][58][59][60][61][62]. In heterostructures, these anomalous processes fundamentally change the behaviour of the electrical and thermal conductance [49].…”
mentioning
confidence: 99%
“…In Josephson junctions, atomic-scale 0 − π transitions [51][52][53][54][55][56] are predicted to occur. The existence of Josephson effects has been experimentally verified [57][58][59][60][61][62], but the remaining theoretical predictions have yet to be explored.…”
mentioning
confidence: 99%